0276 Predictors of return to work 12 months after solid organ transplantation: results from a cohort study in switzerland. (21st August 2017) - Vieux, Laure; Simcox, Amira; Mediouni, Zakia; Wild, Pascal; Koller, Michael; Studer, Regina; Danuser, Brigitta
Abstract : Background: Return to work with or after a chronic disease is not a very well understood process, influenced by a variety of personal, professional, societal and medical factors. The aim of this study is to identify predictors for return to work 12 months after a solid organ transplant, applying a bio-psycho-social model. Methods: Explorative study based on patients included in the Transplant Cohort Study, a national, prospective, multicentric cohort, who underwent a first solid organ transplant (kidney, liver, heart, lung). Bio-psychosocial factors were tested and predictors of return to work identified using logistical regression models. Results: Among the 636 patients included in the study, 49.8% (317) were employed 12 months post transplant. The major predictor for returning to work 12 months post transplant was pre-transplant employment status (OR: 10.8). Accordingly, the population was stratified in employed and unemployed pre transplant groups. Age, self-perceived health (SPH, six months post-transplant) and the transplanted organ were significantly associated with post transplantation employment status in both groups. Additionally, return to work was influenced by education, depression (six month post-transplant) and waiting time in the employed pre transplant group and by invalidity pension in the unemployed pre transplant group. Conclusion: Employment rate pre transplant being highly associated with employment status post transplant, the process promoting return to work should be started well before surgery.